Implementasi Website Sistem Informasi Keluarga (SIGA) dalam Upaya Peningkatan Layanan Pendataan Keluarga pada Kementerian Kependudukan dan Pembangunan Keluarga/BKKBN (Kemendukbangga/BKKBN) - Syamsir Syamsir; Nanda Alya Pratiwi; Naila Salsabila (Journal of Education on Social Science (JESS), 2025)
To improve the quality of family data services, BKKBN has carried out service system reform through the use of information technology. This reform is implemented by developing and applying SIGA as an integrated information system. SIGA serves as a tool for data collection, work mapping, program intervention, and performance measurement across all administrative levels. This study aimed to investigate the implementation of the SIGA website program in an effort to improve the quality of family data collection services at the National Population and Family Planning Board (BKKBN) office, in line with service system reform through the use of information technology. This study reflected fieldwork experiences using a qualitative descriptive approach. Data were obtained through several competent informants at the Ministry of Population and Family Development/BKKBN. Data were analyzed using interactive modeling. The results indicated that through data digitalization, SIGA enables services to become more accurate, efficient, and accessible. However, its implementation still faces technical and human resource readiness challenges. Overall, SIGA is a key element in BKKBN’s service reform efforts, supporting a modern, responsive, and sustainable family data governance system.